Collective Action and Carbon Sequestration in Nepal (Journal of Forest and Livelihood, 2016)
This paper uses forest plot measurements and information on forest collective action to estimate the effects of collective action on four measures of forest quality (e.g., carbon content, tree density, seedling density and canopy cover) in Nepal. Carbon sequestration is of special interest because it may be creditable under Reducing Emmission from Deforestation and Forest Degradation (REDD+). We find that community forest collective action sequesters carbon and appears to support several other forest quality measures. Even though registered community forests sequester more carbon than other forests, we find that non-registered community forests also show evidence of important collective action, with positive effects on forests.Journal of Forest and Livelihood 13(1) May, 2015, page : 1-7